Effect of Gonadotrophin Releasing Hormone (GnRH) on Induction of Ovarian Cyclicity in Pubertal Anoestrus Buffalo Heifers - NAUTIYAL, HEMANT; SHANKAR, UMA; AGARWAL, S K (The Indian Journal of Animal Reproduction, 2023)
Effect of GnRH on induction of ovarian cyclicity was studied on 21 pubertal anoestrus buffalo heifers. Animals were divided into three groups. In the experimental group treated with 1.5 ml GnRH, 85.71% heifers exhibited oestrus within 83.02± 10.04 (66-90) hrs after the GnRH injection. In the second experimental group treated with 2.5 ml GnRH 71.42% heifers exhibited oestrus· within 62.30± 17.22 ( 42-90) hrs after the GnRH injection whereas in the control group 28.5% heifers exhibited oestrus within 90.00±00 (90-90) hrs after normal saline injection. Tfle pregnancy rate in the treated group were 4 / 5 (80%) and 4 / 5 (80%) respectively as compared to 2 / 2 ( 100%). The results indicated thatthe ovarian cyclicity can be induced with GnRH in anoestrus pubertal buffalo heifers.